Evolutionary trend in dental size in fossil orangutans from the Pleistocene of Chongzuo, Guangxi, southern China. Issue 161 (December 2021) - Harrison, Terry; Zhang, Yingqi; Yang, Liyun; Yuan, Zengjian
Abstract: More than 800 isolated teeth of fossil Pongo have been recovered from cave sites in the vicinity of Chongzuo in Guangxi, southern China, ranging from the Early to Late Pleistocene (2.0–0.1 Ma). These collections provide a unique regional window into the evolutionary history of orangutans over a two-million-year period at the northernmost extent of their former geographic range. Here we investigate the nature and timing of the evolutionary change in the dental size of fossil orangutans from Chongzuo. Fossil tooth size (mesiodistal length∗buccolingual breadth) was compared against an extant Pongo pygmaeus standard ( n = 106 individuals). During the course of the Pleistocene, orangutans from southern China exhibited a progressive reduction in overall dental size. Early Pleistocene Pongo has cheek teeth with occlusal areas that are 38.1% larger than those of extant P. pygmaeus . Those from the Middle and Late Pleistocene are 25.2% and 18.9% larger, respectively. Previously, the size difference in dentition between the Early to Middle Pleistocene and Middle to Late Pleistocene samples was used to differentiate time-successive species of Pongo, namely Pongo weidenreichi and Pongo devosi . However, with access to larger samples and better representation of populations through time, the evidence in support of this taxonomic arrangement requires reconsideration. Diminution of the teeth now appears to be a gradual evolutionary transformation rather than a punctuated event. Moreover, the morphological features that distinguish the Chongzuo fossil orangutans from extant Pongo spp. remain uniform throughout the Pleistocene. Retaining P. weidenreichi and P. devosi as anagenetic species remains an option, but, given the current evidence, we consider it preferable to assign all of the fossil orangutans from Chongzuo to P. weidenreichi . Beyond resolving questions of alpha taxonomy, the study of fossil orangutan dental size provides a basis for estimating body mass, which has implications for interpreting the paleobiology of Pleistocene Pongo in southern China.